Infant‐directed speech to infants at risk for dyslexia: A novel cross‐dyad design. (22nd February 2020) - Kalashnikova, Marina; Goswami, Usha; Burnham, Denis
Abstract: When mothers speak to infants at risk for developmental dyslexia, they do not hyperarticulate vowels in their infant‐directed speech (IDS). Here, we used an innovative cross‐dyad design to investigate whether the absence of vowel hyperarticulation in IDS to at‐risk infants is a product of maternal infant‐directed behavior or of infants' parent‐directed cues. Interactions between mothers and infants who were at risk or not at risk for dyslexia were recorded in three conditions: when mothers interacted with (a) their own infants, (b) infants who were not their own but of the same risk status, and (c) infants who were not their own and of the opposite risk status. This design revealed both infant and parent effects. Mothers of not‐at‐risk infants hyperarticulated vowels significantly more when speaking to not‐at‐risk than to at‐risk infants. In contrast, mothers of at‐risk infants hyperarticulated vowels significantly less than NAR mothers, and this was irrespective of infant status. Mothers of not‐at‐risk infants thus adjusted their IDS to the infant's risk status, while mothers of at‐risk infants did not. We suggest that IDS is determined reciprocally by characteristics of both partners in the dyad: Both infant and maternal factors are essential for the vowel hyperarticulation component of IDS.